1995
DOI: 10.1007/bf00003547
|View full text |Cite
|
Sign up to set email alerts
|

Molecular characterisation of Sargassum polycystum and S. siliquosum (Phaeophyta) by polymerase chain reaction (PCR) using random amplified polymorphic DNA (RAPD) primers

Abstract: Genomic DNA was extracted from 13 samples of Sargassum polycystum and S. siliquosum collected from various localities around Peninsular Malaysia and Singapore by using four different extraction methods. The yields and the suitability of the DNA to be used as template for the polymerase chain reaction (PCR) was compared. DNA samples were subjected to PCR analysis by using random primers. Only DNA samples that were extracted using the CTAB method were successfully amplified by random amplified polymorphic DNA (R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0
1

Year Published

1996
1996
2007
2007

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(18 citation statements)
references
References 20 publications
0
17
0
1
Order By: Relevance
“…Although the CTAB method (Shivji et al, 1992;Ho et al, 1995) and the combination of alginic lyase and CTAB (Hu & Zhou, 2001) have been reported successfully to extract DNA from brown algae, they are not suitable for DNA extraction from sporophyte Laminaria japonica. DNA isolated by these two methods was contaminated with large amounts of polysaccharides and RNA, and DNA solution was so viscous that it was difficult to peppete DNA into the sample wells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the CTAB method (Shivji et al, 1992;Ho et al, 1995) and the combination of alginic lyase and CTAB (Hu & Zhou, 2001) have been reported successfully to extract DNA from brown algae, they are not suitable for DNA extraction from sporophyte Laminaria japonica. DNA isolated by these two methods was contaminated with large amounts of polysaccharides and RNA, and DNA solution was so viscous that it was difficult to peppete DNA into the sample wells.…”
Section: Discussionmentioning
confidence: 99%
“…To reduce the effects of viscous polysaccharides, Ho et al (1995) found that DNA extraction from Sargassum polycystum and S. siliquosum using CTAB (cetyltrimethyl ammonium bromide) were amplified successfully by random amplified polymorphic DNA (RAPD-PCR). Hu and Zhou (2001) reported a new extraction method to extract high quality DNA from Laminaria japonica, which involves enzymatic dissociation of sporophyte tissues and subsequent elimination of the remaining polysaccharides using CTAB.…”
Section: Introductionmentioning
confidence: 99%
“…Random amplified polymorphism DNA (RAPD) (Williams et al, 1990;Hadrys et al, 1992) was used successfully in species differentiation on Gracilaria (Meneses, 1996;Lim et al, 2001), Furcellaria (Valatka et al, 2000), Laminaria (Billot et al, 1999) and Sargassum (Ho et al, 1995a(Ho et al, , 1995bPark et al, 1998;Engelen et al, 2001). The objective of this study is to use a combination of morphometric and RAPD analyses to differentiate between the S. baccularia and S. polycystum, which are found in close proximity.…”
Section: Introductionmentioning
confidence: 99%
“…For a general review of this technique, see Weising et al (1995). In seaweed studies, RAPDs have been used for species identification (Patwary et al 1993, Dutcher & Kapraun 1994, Patwary & van der Meer 1994, Ho et al 1995, Gonzalez et al 1996, Meneses 1996, biogeographic studies (van Oppen et al 1994, Pakker et al 1996, and the determination of genetic relatedness among and within populations (Coyer et al 1997). Van Oppen et al (1996) assessed the limits of RAPDs for seaweed biogeography.…”
Section: Introductionmentioning
confidence: 99%